Prevention of core particle depletion in stellarators by turbulence - Thienpondt, H; García-Regaña, JM; Calvo, I; Alonso, JA; Velasco, JL; González-Jerez, A; Barnes, M; Brunner, K; Ford, O; Fuchert, G; Knauer, J; Pasch, E; et al. (American Physical Society, 2023)
In reactor-relevant plasmas, neoclassical transport drives an outward particle flux in the core of large stellarators and predicts strongly hollow density profiles. However, this theoretical prediction is contradicted by experiments. In particular, in Wendelstein 7-X, the first large optimized stellarator, flat or weakly peaked density profiles are generally measured, indicating that neoclassical theory is not sufficient and that an inward contribution to the particle flux is missing in the core. In this Research Letter, it is shown that the turbulent contribution to the particle flux can explain the difference between experimental measurements and neoclassical predictions. The results of this Research Letter also prove that theoretical and numerical tools are approaching the level of maturity needed for the prediction of equilibrium density profiles in stellarator plasmas, which is a fundamental requirement for the design of operation scenarios of present devices and future reactors.